A comprehensive review on counter electrodes for dye sensitized solar cells: A special focus on Pt-TCO free counter electrodes. (1st November 2018) - Ahmed, Usman; Alizadeh, Mahdi; Rahim, Nasrudin Abd; Shahabuddin, Syed; Ahmed, Muhammad Shakeel; Pandey, A.K.
Highlights: Compendium on switching from Pt based CE to naturally available materials for CE. Systematically reviews on the CE in DSSCs with special focus on Pt-TCO free CE. Synthesis and fabrication methods of various CE has been presented. Abstract: Among all PV devices, DSSCs are believed to be one of the most promising devices, owing to their low cost, facile methods of fabrication and eco-friendly nature. Several components such are titanium dioxide/metal oxide-based photoanode, platinum/composite material based counter electrode and sensitizing dye along with the electrolyte are the basic components which effects the performance of DSSCs. Counter electrode collects the electron from an external circuit and helps in the regeneration of dye by oxidation-reduction of electrolyte, which significantly effects the overall performance of PV devices. Several materials such as carbonaceous materials, conducting polymers, oxides, and sulfides have been investigated as the low cost and highly stable material for the potential replacement for an expensive Pt-based counter electrode in DSSCs. In this Review, an attempt has been made to present recent achievements to replace Platinum (Pt) counter electrode with other inexpensive and earth abundant materials for DSSCs. This article systematically reviews the counter electrodes in DSSCs and provides review focused on Pt-TCO free counter electrodes. The main problems and challenges such as synthesis and fabrication of various CE, commercialization of DSSCs are addressed in detail with a conclusion and proposition section.